Who hid the Easter eggs? - Vainio, Pirkko (New York : NorthSouth, 2010)
Harry the squirrel must save the annual Easter egg hunt when someone takes a keen interest in the hidden eggs.
"First published in Switzerland under the title Nico rettet die Ostereier"--Colophon.
2.9
K-3
K-3
Keywords: Easter eggs -- Juvenile fiction; Easter -- Juvenile fiction; Squirrels -- Juvenile fiction; Easter eggs -- Fiction; Easter -- Fiction; Squirrels -- Fiction; Easter eggs -- Fiction; Easter -- Fiction; Squirrels -- Fiction; Picture books for children